Experiências sobre a implementação de Balanced Scorecard em empresas no Brasil: estudos de caso. - Canevarolo, Maria Estela Antonioli Pisani (2004)
This dissertation aims to investigate the implementation of Balanced Scorecard (BSC) in two large companies that operates in Brazil. The realization of the inadequacy of traditional performance measurement systems based on Managerial Accounting that occurred from the beginning of the twenty-century due to the new external and internal operational conditions faced by the most of the companies, many performance measurement systems have been proposed. The most visible result of such revolution is the BSC applied worldwide as well as in Brazil. The BSC has evolved from a performance measurement system to a strategic management system. With relation to Brazil, it is known the growing number of companies adopting the BSC but little empirical research can be found on implementation. The adopted research method was the case study in order to capture the different perspectives on implementation, by conducting semi-structured interviews with people involved in it. Furthermore, the investigation allowed observation of concrete aspects of the implementation. The empirical findings show the implementation of third generation BSC, that is, BSC applied as strategic management system in both companies. With the BSC implementation the culture of strategic planning was implemented or strengthened in the studied companies. The information technology has played a very important role to communicate the strategy but alone it was not enough being also necessary, among other aspects, a good communication plan and the top management support. Also, it was observed that the stakeholder vision regarding performance measurement was limited. Although the BSC is a simple concept it was hard to be implemented because it required the involvement of many people who did not have the same understanding of strategy.